2022
DOI: 10.3389/fpubh.2021.800702
|View full text |Cite
|
Sign up to set email alerts
|

Value-Based Healthcare From the Perspective of the Healthcare Professional: A Systematic Literature Review

Abstract: Introduction: Healthcare systems increasingly move toward “value-based healthcare” (VBHC), aiming to further improve quality and performance of care as well as the sustainable use of resources. Evidence about healthcare professionals' contributions to VBHC, experienced job demands and resources as well as employee well-being in VBHC is scattered. This systematic review synthesizes this evidence by exploring how VBHC relates to the healthcare professional, and vice versa.Method: Seven databases were systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 80 publications
(468 reference statements)
0
11
0
1
Order By: Relevance
“…This could imply that there has mainly been a bottom-up approach for the set-up of VI teams. Meanwhile, the importance of strong leadership supportive of VBHC implementation has been highlighted several times in literature as shown by a literature review [ 30 ]. This suggests the need for improved organization-wide policies on VBHC and improved communication on these policies towards staff members [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could imply that there has mainly been a bottom-up approach for the set-up of VI teams. Meanwhile, the importance of strong leadership supportive of VBHC implementation has been highlighted several times in literature as shown by a literature review [ 30 ]. This suggests the need for improved organization-wide policies on VBHC and improved communication on these policies towards staff members [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent review suggests that discussing value-based health care with patients, particularly in regard to costs and the option of nontreatment, can be difficult. 39 Additionally, maintaining a collegial relationship with nurses can be viewed through the lens of “socialization as interaction,” where roles are constructed through interactions and discourse. 40 This relationship may sometimes result in fewer day-to-day value-based decisions made by residents since nurses provide advocacy for their patients’ individual health needs.…”
Section: Discussionmentioning
confidence: 99%
“…A prior systematic review showed the importance of considering the health professionals’ perspective 60 in the transition to VBHC systems, and we hypothesise that the perspective of citizens may also be relevant, but felt this to be outside the scope of our review, focusing on patient-centredness.…”
Section: Discussionmentioning
confidence: 99%